THE MOVES AND STEPS IN THE LITERATURE REVIEW AND DISCUSSION SECTIONS IN THE FOUR MASTER’S DEGREE THESES - La Ode Muh. Idrus Hamid B.; Wa Ode Nur Maulid (Universitas Sembilanbelas November Kolaka, 2017)
The purpose of this research was to identify moves and steps in the Literature Review and Findings / Discussion chapter of four Master’s Degree theses namely JA, LY, ML, and MM. In analyzing the moves and steps in the Literature Review (LR) and Discussion in this research, the researchers used two kinds of framework namely Kwan (2006) framework and Yang Allison (2003) framework. Kwan framework was used to analyze the moves and steps in the Literature Review, while Yang Alison’s framework was used to analyze moves and steps in the Discussion chapter. It was found that the most frequently used in the LR was Move 1 (Establishing one of the territory of one’s own research), Strategy A (surveying the non-research-related phenomena or knowledge claims) included definition or explanations of terminology, constructs and theories. The authors of four Master Degree’s theses used Move 1 to present the theories and definition of terms. Then, in the Findings/Discussions, the most frequently used is Move 2 (Reporting Result). The authors used Move 2 in presenting the results of their study (research).